2016
DOI: 10.1128/jvi.03267-15
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Specific Amino Acid Residues That Make Hamster DPP4 Functional as a Receptor for Middle East Respiratory Syndrome Coronavirus

Abstract: The novel emerging coronavirus Middle East respiratory syndrome coronavirus (MERS-CoV) binds to its receptor, dipeptidyl peptidase 4 (DPP4), via 14 interacting amino acids. We previously showed that if the five interacting amino acids which differ between hamster and human DPP4 are changed to the residues found in human DPP4, hamster DPP4 does act as a receptor. Here, we show that the functionality of hamster DPP4 as a receptor is severely decreased if less than 4 out of 5 amino acids are changed. IMPORTANCETh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In the case of haDPP4, the L288 amino acid identity is conserved between the hamster and human sequences, suggesting that different determinants in haDPP4 and mDPP4 are responsible for blocking MERS-CoV infection. This is consistent with prior studies which identified several amino acid differences between hDPP4 and haDPP4 in blade V that were required to support MERS-CoV infection (17). Therefore, we asked whether specific changes in blade V of haDPP4 could allow it to act as a functional MERS-CoV receptor in combination with the blade IV glycosylation knockout mutation.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In the case of haDPP4, the L288 amino acid identity is conserved between the hamster and human sequences, suggesting that different determinants in haDPP4 and mDPP4 are responsible for blocking MERS-CoV infection. This is consistent with prior studies which identified several amino acid differences between hDPP4 and haDPP4 in blade V that were required to support MERS-CoV infection (17). Therefore, we asked whether specific changes in blade V of haDPP4 could allow it to act as a functional MERS-CoV receptor in combination with the blade IV glycosylation knockout mutation.…”
Section: Resultssupporting
confidence: 86%
“…These values can be compared to amino acid sequence identity values of 85%, 88%, 85%, and 87%, respectively. The high sequence similarities and predicted structural similarities between hDPP4 and these orthologs suggest that they can likely act as backbones to support MERS-CoV infection, consistent with previous DPP4 ortholog work (15,17).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Structural studies have shown that this interaction relies on multiple contact points (Lu et al, 2013;Song et al, 2014;Wang et al, 2013). Our group has previously demonstrated that hamster DPP4 contains variation in these contact points, which prevents MERS-CoV replication (van van Doremalen et al, 2016). Other genetic variation responsible for the glycosylation of DPP4 in mice, hamsters, ferrets, and guinea pigs forms an additional block to the interaction with MERS-CoV spike (Cockrell et al, 2014;Peck et al, 2017).…”
Section: Introductionmentioning
confidence: 99%